2014
DOI: 10.7732/kjpr.2014.27.3.242
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated Transformation via Somatic Embryogenesis System in Korean fir (Abies koreana Wil.), A Korean Native Conifer

Abstract: -This study was conducted to establish an efficient transformation system by using somatic embryogenesis in an important Korean native conifer, Korean fir (Abies koreana). Embryogenic masses were induced from mature zygotic embryos of the Korean fir on Schenk and Hildebrandt medium, which was supplemented with thidiazuron. For genetic transformation, the embryogenic masses were co-cultivated with a disarmed Agrobacterium tumefaciens strain C58/pMP90 containing the plasmid vector pBIV10 or LBA4404 containing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…During the last two decades, progress has been achieved in genetic transformation studies of conifer species, including representatives of the genus Abies . Find et al (2005) reported successful genetic transformation of A. nordmanniana using the biolistic method and Lee et al (2014) obtained transformed embryogenic tissue of A. koreana Wil. using Agrobacterium tumefaciens mediated transformation.…”
Section: Somatic Embryogenesis In the Hybrids Abies Alba X A Cephalomentioning
confidence: 99%
See 1 more Smart Citation
“…During the last two decades, progress has been achieved in genetic transformation studies of conifer species, including representatives of the genus Abies . Find et al (2005) reported successful genetic transformation of A. nordmanniana using the biolistic method and Lee et al (2014) obtained transformed embryogenic tissue of A. koreana Wil. using Agrobacterium tumefaciens mediated transformation.…”
Section: Somatic Embryogenesis In the Hybrids Abies Alba X A Cephalomentioning
confidence: 99%
“…A prerequisite for successful genetic transformation is using plant material with high regeneration ability. Rapidly growing embryogenic tissue producing early somatic embryos with the ability to regenerate somatic seedlings represents such material (Lee et al, 2014). The success of transformation in A. koreana Wil.…”
Section: Somatic Embryogenesis In the Hybrids Abies Alba X A Cephalomentioning
confidence: 99%
“…Agrobacterium tumefaciens stands as one of the primary strains used in plant genetic transformation research. Transgenic plants were successfully generated in Abies nephrolepis, Pinus elliottii and Pinus radiata through the utilization of Agrobacterium strains including LBA4404, GV3101, and EHA105 [18][19][20]. Agrobacterium rhizogenes is another commonly used type of Agrobacterium.…”
Section: Common Tree Genetic Transformation Techniquesmentioning
confidence: 99%
“…Ever since the first report on the Agrobacterium-mediated transfer of herbicide tolerant gene to poplars (Fillatti et al, 1987), there has been considerable interest in the application of GE to forest trees by Agrobacterium-mediated or biolistic methods. During the last three decades, a number of forest trees have been genetically engineered with a variety of different recombinant genes, using tissues derived from organogenesis (leaf discs, microshoots, different tissues/organs) and somatic embryogenesis (embryonal cells/mass) for the production of transgenic trees (Charest and Michel, 1991;Fladung, Muhs, Ahuja, 1996;Ahuja, 2000;Trontin et al, 2002Trontin et al, , 2007 Lee et al, 2014;Uddenberg et al, 2016). The first wave of GE involved the transfer of "foreign" genes (mostly bacterial genes) used as reporter genes to monitor the integration and expression of transgenes in forest trees.…”
Section: Genetic Engineering In Treesmentioning
confidence: 99%